2016
DOI: 10.5713/ajas.15.0775
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and effect of selection at the mitochondrial hypervariable region in major Nigerian indigenous goat breeds

Abstract: Mitochondrial DNA (mtDNA) hypervariable region 1 ( HV1) sequences of three Nigerian indigenous goat breeds; West African Dwarf (WAD), Red Sokoto (RS) and Sahel were used to investigate the genetic diversity and effect of selection between and among these populations. Deoxyribonucleic acid (DNA) of Nigerian indigenous chicken was extracted from blood samples collected and preserved on Fast Technology for Analysis (FTA) paper. The extracted DNA were amplified and sequenced with predefined mitochondria (mtDNA) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Among the twelve breeds sequences used for this analysis Guanzhong and Xinong Saanen had 100 percent nucleotide identity having the closest value of 0.000 and the highest was observed at 0.574 between Red Sokoto and Guanzhong, Xinong Saanen, Lehzi black. Based on the polymorphisms earlier reported in this study we observed a low pair-wise distance of 0.003 between Red Sokoto and Sahel goat breeds which compares favourable with findings of other studies estimate for Red Sokoto and Sahel (Murital et al, 2015;Udeh, 2015;Ajibike et al, 2016;Ajayi et al, 2016;Ojo et al, 2017). The low genetic distance estimates obtained between Red Sokoto and Sahel from different molecular markers could be attributed to migration, high degree of miscegenation or high gene flow, geographical adaptation.…”
Section: Genetic Distance Between Red Sokoto Sahel and Other Goat Brsupporting
confidence: 89%
“…Among the twelve breeds sequences used for this analysis Guanzhong and Xinong Saanen had 100 percent nucleotide identity having the closest value of 0.000 and the highest was observed at 0.574 between Red Sokoto and Guanzhong, Xinong Saanen, Lehzi black. Based on the polymorphisms earlier reported in this study we observed a low pair-wise distance of 0.003 between Red Sokoto and Sahel goat breeds which compares favourable with findings of other studies estimate for Red Sokoto and Sahel (Murital et al, 2015;Udeh, 2015;Ajibike et al, 2016;Ajayi et al, 2016;Ojo et al, 2017). The low genetic distance estimates obtained between Red Sokoto and Sahel from different molecular markers could be attributed to migration, high degree of miscegenation or high gene flow, geographical adaptation.…”
Section: Genetic Distance Between Red Sokoto Sahel and Other Goat Brsupporting
confidence: 89%
“…Goats play an important role in the life of small-holder farmers via their ability to convert lowcost feed resource to high value products (meat and milk) (Aregawi et al, 2013). Goat is one of the most important, adaptable and geographically widespread livestock species, which provides a good source of meat, milk and other by-products and is therefore referred to as "poor man's cow" (Ajibike et al, 2016). The role of goats in providing protein to humans is increasingly being recognized.…”
Section: Introductionmentioning
confidence: 99%